2021
DOI: 10.3389/fneur.2021.666438
|View full text |Cite
|
Sign up to set email alerts
|

Attention-Demanding Cognitive Tasks Worsen Postural Control in Patients With Cervical Dystonia: A Case-Control Study

Abstract: Background: Patients with cervical dystonia (CD) show impaired postural control, balance, and gait, likely due to abnormal head postures and sensorimotor disturbances. However, until now no study has investigated whether attention-demanding activity worsens postural control and balance in CD patients.Objective: To investigate whether patients with CD show cognitive-motor interference (CMI), a specific kind of dual-task interference that occurs during the simultaneous execution of a cognitive and motor task. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
2
7
0
Order By: Relevance
“…Eventually, on both feet, a larger Pmax on the Rf area (left = 67.3 KPa; right = 63.3 KPa) with respect to the Ff one was found in agreement with [ 29 ], while a larger Pmean in Ff with respect to other two regions was found with a median value of 59.1 KPa on the left side and 69.9 KPa on the right one. Finally, normal median values of CoPsa (28.8 mm2), LSF (4.7 m−1), and CP speed (3.4 mm/s) in OE condition confirmed the normal 244 range values found in [ 30 , 31 , 32 ], respectively, in healthy, young subjects.…”
Section: Discussionsupporting
confidence: 75%
“…Eventually, on both feet, a larger Pmax on the Rf area (left = 67.3 KPa; right = 63.3 KPa) with respect to the Ff one was found in agreement with [ 29 ], while a larger Pmean in Ff with respect to other two regions was found with a median value of 59.1 KPa on the left side and 69.9 KPa on the right one. Finally, normal median values of CoPsa (28.8 mm2), LSF (4.7 m−1), and CP speed (3.4 mm/s) in OE condition confirmed the normal 244 range values found in [ 30 , 31 , 32 ], respectively, in healthy, young subjects.…”
Section: Discussionsupporting
confidence: 75%
“…Dual tasking is also dependent on higher cognitive processes such as executive functions required for planning and executing complex task, suggesting prominent cortical involvement, with some suggesting that impaired dual tasking suggests a reduction in contingency or reserve in those regions involved in dual tasking. Again, most studies have focused on AOIFCD, identifying impaired postural control with increasing cognitive task complexity compared to controls (p < 0.0001) with neither dystonia motor severity nor the presence of a tremor being significantly associated with the degree of impaired stability [59]. Further studies have extended this to evaluate the impact of dual tasking on both balance and gait, again examining those with AOIFCD (n = 17), compared to controls (n = 19), at normal walking speed, fast walking, cognitive dual task, and obstacle negotiation.…”
Section: Dual Taskingmentioning
confidence: 99%
“…In idiopathic dystonia, difficulties in performing DT were firstly observed by Jahanshahi et al ( 2003 ) where patients showed a decrement of tapping task during a concurrent task performed with the other hand. Two recent studies (Demir et al 2020 ; Baione et al 2021 ) also reported cognitive DT interference in CD subjects, showing a decrement of postural control during the concomitant execution of an attention-demanding tasks. In line with these results, here we found that the ability to walk while carrying out another task is impaired in CD subjects, suggesting that there are fewer attentional resources available for simultaneous performance of secondary tasks.…”
Section: Discussionmentioning
confidence: 92%
“…Conversely, only two studies investigated cognitive-motor interference in CD patients (Demir et al 2020 ; Baione et al 2021 ). As an example, Baione et al ( 2021 ), based on the hypothesis that balance disturbances in CD may be associated with a reduction of the attentional resources available for simultaneous performance of secondary tasks, investigated whether postural control would be worsened by a concomitant execution of attention-demanding cognitive task.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation